Recent advances in early diagnosis and treatment of T1D with miRNAs - Zhang, Xinling; Qiu, Yuting; Liu, Dong-ang; Hu, Ruiyao; Chen, Shiyu; Xu, Yue; Chen, Keyi; Yuan, Jinghua; Li, Xiaoping (Frontiers in Endocrinology, 2025)
Type 1 diabetes (T1D) is an autoimmune disease characterized by T cell-mediated destruction of pancreatic β-cells and is one of the most common chronic diseases in adults and children. In recent years, the incidence of T1D has been increasing worldwide. Currently, the diagnosis of T1D relies on clinical manifestations and autoantibody detection, with a lack of early predictive biomarkers. MicroRNAs (miRNAs), as crucial post-transcriptional regulatory factors, which are involved in various biological processes, including cell division, proliferation, differentiation, development, and metabolism. Additionally, miRNAs participate in the regulation of inflammatory complications in T1D, and their aberrant expression is closely associated with the disease. The stability of miRNAs makes them potential candidates for early diagnostic biomarkers and therapeutic targets in T1D. This paper discusses the pathogenesis of T1D and the potential applications of miRNAs in early diagnosis and interventional therapy. It provides references for advancing precision diagnosis and personalized treatment strategies through more profound miRNA research in the future.